Readability of patient information and consent documents in rheumatological studies. Issue 1 (December 2016) - Hamnes, Bente; van Eijk-Hustings, Yvonne; Primdahl, Jette
Abstract Background Before participation in medical research an informed consent must be obtained. This study investigates whether the readability of patient information and consent documents (PICDs) corresponds to the average educational level of participants in rheumatological studies in the Netherlands, Denmark, and Norway. Methods 24 PICDs from studies were collected and readability was assessed independently using the Gunning's Fog Index (FOG) and Simple Measure of Gobbledygook (SMOG) grading. Results The mean score for the FOG and SMOG grades were 14.2 (9.0–19.0) and 14.2 (12–17) respectively. The mean FOG and SMOG grades were 12.7 and 13.3 in the Dutch studies, 15.0 and 14.9 in the Danish studies, and 14.6 and 14.3 in the Norwegian studies, respectively. Out of the 2865 participants, more than 57 % had a lower educational level than the highest readability score calculated in the individual study. Conclusions As the readability level of the PICDs did not match the participants' educational level, consent may not have been valid, as the participants may have had a limited understanding of what they agreed to participate in. There should be more focus on the readability of PICDs. National guidelines for how to write clear and unambiguous PICDs in simple and easily understandable language could increase the focus on the readability of PICD.